Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)=\(\frac{9}{4}\)
b)=\(\frac{89}{50}\)
c)=\(\frac{7}{9}\)
d)=\(\frac{26}{7}\)
khỏi chép đề nha
a\Câu 1:
200 : ( 15 - x ) = 15 + 5
200 : ( 15 - x ) = 20
15 - x = 200 : 20
15 - x = 10
x = 15 - 10
x = 5
Câu 2:
63 : ( x - 5 ) = 22 -1
63 : ( x - 5 ) = 21
x - 5 = 63 : 21
x - 5 = 3
x = 3 + 5
x = 8
3/4 x 8/5 x 5/9 = 3/4 x 8/5 x 5/9 = 1/1 x 2/1 x 1/3 = 2/3
6/4 : 3/14 : 1/2 = 6/4 x 14/3 x 2/1 = 2/2 x 14/1 x 1/1 = 14
k mk nha
\(\frac{12}{17}:4=\frac{12}{17}.\frac{1}{4}=\frac{3}{17}.\frac{1}{1}=\frac{3}{17}\)
\(12:\frac{6}{13}=12.\frac{13}{6}=2.\frac{13}{1}=26\)
\(9:\frac{3}{5}.\frac{4}{15}=9.\frac{5}{3}.\frac{4}{15}=3.\frac{5}{1}.\frac{4}{15}=\frac{15}{1}.\frac{4}{15}=\frac{1}{1}.\frac{4}{1}=4\)
Hok tốt!!!
6 2/7 + 7 3/5 + 8 6/9 + 9 1/4 + 2/5 + 5/7 + 1/3 x 3/4 + 1967
= 44/7 + 38/5 + 78/9 + 37/4 + 2/5 + 5/7 + 1/3 + 1967
= ( 44/7 + 5/7 ) + ( 38/5 + 2/5 ) + ( 26/3 + 1/3 ) + ( 37/4 + 3/4 ) +1967
= 7 + 8 + 9 + 10 + 1967
= 15 + 9 + 10 + 1967
= 24 + 10 + 1967
= 34 + 1967
= 2001
\(25\frac{2}{13}-\left(\frac{15}{17}+15\frac{2}{3}\right)=\frac{327}{13}-\left(\frac{15}{17}+\frac{47}{3}\right)\)
\(=\frac{327}{13}-\frac{844}{51}\)
\(=\frac{5705}{663}\)
\(\frac{5}{30}+\frac{15}{90}+\frac{250}{150}+\frac{350}{210}+\frac{45}{270}=\frac{1}{6}+\frac{1}{6}+\frac{5}{3}+\frac{5}{3}+\frac{1}{6}\)
\(=\frac{3}{6}+\frac{10}{3}\)
\(=\frac{1}{2}+\frac{10}{3}\)
\(=\frac{23}{6}\)
\(3\frac{1}{11}.\frac{27}{46}.1\frac{6}{17}.2\frac{4}{9}=\frac{34}{11}.\frac{27}{46}.\frac{23}{17}.\frac{22}{9}\)
\(=\frac{68}{9}.\frac{27}{34}\)
\(=6\)
\(\frac{2}{3}\)x \(\frac{5}{8}\)x \(\frac{8}{15}\)= \(\frac{2}{3}\)x \(\frac{1}{15}\)= \(\frac{2}{45}\)
\(\frac{22}{5}\)x \(12\)x \(\frac{20}{40}\)= \(\frac{22}{5}\)x \(12\)x \(\frac{1}{2}\)= \(\frac{22}{5}\)x 6 = \(\frac{122}{5}\)
\(\frac{7}{2}\)x \(\frac{26}{7}\)x \(\frac{4}{13}\)= \(\frac{91}{7}\)x \(\frac{4}{13}\)
[4\(\dfrac{1}{5}\) - 2\(\dfrac{2}{5}\)] x 8\(\dfrac{5}{6}\)
= [\(\dfrac{21}{5}\) - \(\dfrac{12}{5}\)] x \(\dfrac{53}{6}\)
= \(\dfrac{9}{5}\) x \(\dfrac{53}{6}\)
= \(\dfrac{159}{10}\)
[5\(\dfrac{1}{3}\) - 2\(\dfrac{2}{3}\)]: \(\dfrac{3}{7}\)
= [\(\dfrac{16}{3}\) - \(\dfrac{8}{3}\)]: \(\dfrac{3}{7}\)
= \(\dfrac{8}{3}\) : \(\dfrac{3}{7}\)
= \(\dfrac{56}{9}\)